Latin American Liberation Theology - Tombs, David (Religion in the Americas, 2002)
David Tombs offers an accessible introduction to the theological challenges raised by Latin American Liberation from its emergence in the 1960s to its 'decade of crisis' in the 1990s. This work traces the distinct developments of liberation thought through the decades, and is crucial to understanding liberation theology and its legacies.; Readership: All who are interested in church history, Latin American studies and the emergence of political and contextual Christian theologies over the last four decades.